2009
DOI: 10.1159/000245156
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Cytokines and Chemokines in Alzheimer’s Disease

Abstract: A chronic inflammatory process has been implicated in the neuropathology of Alzheimer’s disease (AD). The present review focuses on the current knowledge of circulating serum and plasma biomarkers of AD that are linked to inflammatory reactions. There is abundant evidence that inflammatory mechanisms within the central nervous system contribute to cognitive impairment via cytokine-mediated interactions between neurons and glial cells. Interleukins 1, 4, 6, 10, 12, 16, and 18, tumour necrosis factor, and severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 89 publications
3
75
1
5
Order By: Relevance
“…The phagocytosed fibrillar amyloid beta peptide within microglia activates NLRP3 through lysosomal degradation leading to activation of caspase 1 that induces maturation and secretion of pro-inflammatory cytokines IL-1β and IL-18 [41,154]. However, independent of the brain immune response, raised levels of circulating proinflammatory cytokines have been generally reported in AD subjects in both longitudinal as well as case-control studies, though significant variability has also been noted [155,156,157,158]. A systematic meta-analysis of published reports has clearly shown that raised serum levels of IL-6, TNF-α and IL-1 are associated with increased risk of AD [159].…”
Section: Proinflammatory Cytokinesmentioning
confidence: 99%
“…The phagocytosed fibrillar amyloid beta peptide within microglia activates NLRP3 through lysosomal degradation leading to activation of caspase 1 that induces maturation and secretion of pro-inflammatory cytokines IL-1β and IL-18 [41,154]. However, independent of the brain immune response, raised levels of circulating proinflammatory cytokines have been generally reported in AD subjects in both longitudinal as well as case-control studies, though significant variability has also been noted [155,156,157,158]. A systematic meta-analysis of published reports has clearly shown that raised serum levels of IL-6, TNF-α and IL-1 are associated with increased risk of AD [159].…”
Section: Proinflammatory Cytokinesmentioning
confidence: 99%
“…Several epidemiological and clinical studies have suggested that inflammation may have an important role in dementia, including AD pathogenesis (1)(2)(3)(4)(5). Acute phase response to damaged tissue, expressing amyloid precursor protein, and gene polymorphisms of several inflammatory mediators are some hypotheses suggesting a role of inflammation in AD (6). Several longitudinal studies have also shown that inflammatory markers are related to dementia (2)(3)(4)7).…”
Section: Introductionmentioning
confidence: 99%
“…The chemokines constitute a large family of molecules that induces chemotaxis, leukocytes extravasation, and modulation of a variety of leukocytes functions 12 . There is growing evidence that chemokines and chemokine receptors are up-regulated in resident central nervous system (CNS) cells during AD, which may contribute to plaque-associated inflammation and neurodegeneration 13 . Of these, CCL2 is a member of the CC chemokine family that plays a significant role in inflammatory processes, including atherosclerosis and neurodegenerative disorders 14 .…”
mentioning
confidence: 99%